Ferramentas moleculares para a detecção e genotipagem do Trypanosoma cruzi: aplicação em estudos populacionais do parasito e da epidemiologia da doença de Chagas cardíaca - Marcela Segatto do Carmo (2013)
Chagas disease is still responsible for high morbidity and mortality rates in Latin America. Trypanosoma cruzi, its etiological agent, is a very polymorphic species and has recently been classified into six major lineages or DTUs (TcI-VI). The epidemiological features associated with different DTUs are not well defined, but there is already evidence of association with their geographical distribution, transmission cycles and clinical aspects of the disease. However, more than a century after the discovery of Chagas disease, many questions still need to be clarified regarding its pathogenesis, diagnosis and treatment. The efforts of our research group have been focused on the development of methodologies for the characterization of T. cruzi and its application in the study of molecular epidemiology of Chagas disease. A few years ago we proposed the Clonal Histotropic Model of Chagas disease in attempt to explain difficulties in demonstrating tight correlation between genetic aspects of the parasite and the clinical outcome of patients. Three aspects constitute the basis of this model: natural populations of T. cruzi are multiclonal; distinct parasite clones have differential tissue tropisms, and conventional methods of analysis imply the in vitro growth of isolated parasite populations, which may favor growth of some individuals. In this work we intended to develop or optimize molecular procedures to elucidate the complexity of T. cruzi populations both in vitro and those directly present in tissues of patients whelming severe chronic Chagas heart disease. To dissect the complexity of T. cruzi isolates, we adapted a method originally described for analyzing single spermatozoids, to sort and to characterize the parasite single cells. This approach allowed us to completely identify the complexity of three natural T. cruzi isolates and to estimate the relative contribution of each subpopulation. For example, it was possible, for the first time, to identify and quantify the presence of clones similar to Be-62 inside the Be-78 strain, both isolated from Berenice, Carlos Chagas first patient carrier of "Chagas malady". Furthermore, this methodology has settled the controversy regarding multiclonality X aneuploidy for T. cruzi populations. Another aspect investigated was the T. cruzi reproduction mode. Due to the lack of evidence of sexuality in T. cruzi, it has been widely accepted that the parasite's reproduction is essentially clonal with infrequent genetic recombination. Based on nuclear and mitochondrial markers and population genetic parameters, we analyzed, in a collaborative work with two other students from the Bioinformatics and Parasitology PhD programs, two groups of T. cruzi isolates: one from different regions of Latin America and other obtained exclusively from patients belonging to the state of Minas Gerais. Our results, unlike those generally found in literature, does not support an essentially clonal population structure for T. cruzi, at least for TcII coexisting in the same geographic area, suggesting that genetic exchange between geographically closely related strains are more frequent than initially expected. Regarding the variable clinical course of Chagas disease, cardiac involvement is in general the most serious and frequent manifestation. Heart transplantation (HTx) is one of the few alternatives for end-stage chronic Chagas heart disease (CHD), yet the reactivation of the infection remains a major complication. In the last six years, more than 100 HTx were carried out in the UFMG hospital and of those, about 50% of patients were suffering from CHD. After HTx, patients undergo periodic biopsies to monitor transplant rejection and reactivation of Chagas disease and on average 50% of the transplanted patients develop reactivation of the infection. As amastigotes are rarely found in histopathological analyses of the biopsies is very difficult to get differential diagnosis between the inflammatory process resulting from allograft rejection and infection reactivation. To overcome these limitations our aim was to develop PCR-based strategies for the identification and characterization of T. cruzi DNA in the explanted hearts, follow-up endomyocardial biopsies and other tissues obtained from the transplanted patients. A total of 42 patients were examined so far, totaling 430 samples. DNA of T. cruzi was detected in 120 samples. In 57 samples we found the presence of TcII, one case of TcVI, one case partially identified as TcV or TcVI, 27 as TcII or TcVI, one mixed infection of TcII + TcVI, and three samples with TcI. We demonstrated for the first time the presence of T. cruzi in the adipose tissue of patients with CHD, suggesting that this tissue may be functioning as reservoir, which contributes to the recrudescence of infection. Besides the genotyping, the characterization of the genetic diversity of T. cruzi populations presented in the patients tissues was made by LSSP-PCR. We found polymorphisms in kDNA signatures among parasites from different patients and even in different cardiac sections of the same patient, indicating the presence of more than one T. cruzi clone simultaneously infecting the same patient. The LSSP-PCR technique has been widely used to study the genetic diversity of T. cruzi, but after a survey in the literature we found that different primers, although published with similar names, have been used for the polymorphism analyses of T. cruzi kDNA. To assess the impact of the primer sequence on the profiles obtained by LSSP-PCR we compared the kDNA fingerprint of three T. cruzi reference strains using eight different primers. The results clearly showed that even small changes in the oligonucleotides sequence could significantly alter the kDNA signature of a strain. Finally, in a retrospective and blinded study with nine patients, six who had already reactivated the infection and three that until two years after HTx have not experienced reactivation, we demonstrated that the molecular diagnosis strategy herein proposed is suitable for the early detection of infection reactivation. Positive results were detected within the first follow-up biopsies, preceding 1-18 months the clinical reactivation. These results indicate that the use of PCR targeting minicircles and rDNA 24S is a good strategy to the early diagnosis of Chagas disease reactivation with potential to assist physicians in treatment decisions before onset of reactivation